معوقات الاستثمار الأجنبي المباشر في القطاع السياحي في الجزائر - بوشلالق سليم حموش هشام (المسيلة, 2022)
رغم الصعوبات الجمة التي يعني منها القطاع السياحي في إستقطاب الإستثمار الأجنبي المباشر، على الرغم من التقنيات المتعاقبة التي مرّ بها هذا القطاع منذ فجر الإستقلال و إلى غاية يومنا هذا، والتي تضمنت جملة من الضمانات و الإمتيازات الممنوحة للمستثمرين محليين منهم وأجانب، إلاّ أن الملاحظة أن القطاع لايزال يروح مكانه، السبب الذي دفع الدولة الجزائرية لإعتماد المخططات التوجيهية تعكس الإرادة السياسية للنهوض بهذا الرافد البديل عن قطاع المحروقات، لذلك فقد عمدت الحكومة الجزائرية إلى توفير بيئة مشجعة للإستثمار السياحي، كتقديم تسهيلات مختلفة خاصة ما تعلق منها بجانب التمويل ومنح الرخص والأوعية العقارية، بما يسرع من تجسيد المستثمرين لمشاريعيهم على أرض الواقع. ما يجدر التنويه إليه أنّ الدولة مطالبة بتوفير بيئة نزيهة تحتوي على مقومات العدالة الشفافية والمساواة دون أن ننسى الدور الهام لتطوير الإطار التشريعي والقانوني والإستثمار في الموارد البشرية وعامل الردع كأهم العوامل المحفزة لتطوير آفاق الإستثمار الذي تشده الجزائر. ثانيا: بالإنجليزية Despite the great difficulties that the tourism sector means in attracting FDI In spite of successive rationing in the sector from the dawn of independence to the present day, Which included a number of guarantees and concessions granted to investors locally and foreigners However, the observation that the sector is still in its place reflects the Algerian State's political will to promote this alternative refuge in the burning sector. The Algerian Government has therefore provided an encouraging environment for tourism investment. The provision of various facilities, especially those related to the financing side and the granting of licences and real estate receptacles, accelerating investors' incarnation of their projects on the ground. It should be noted that the State is required to provide a fair and equitable environment that contains the elements of justice, transparency and equality, without forgetting the important role played by the development of the legislative and legal framework, investment in human resources and deterrence, as the most important catalyst for the development of Algeria's investment prospects.
Keywords: معوقات -الاستثمار الأجنبي المباشر- القطاع السياحي- الجزائر